Tourism management for financial access in Sub-Saharan Africa: Inequality thresholds - Simplice Asongu; Mushfiqur Rahman; Okeoma J.-P. Okeke; Afzal S. Munna (African Governance and Development Institute (AGDI), 2021)
The study provides insights into how tourism can be managed to improve financial access in sub-Saharan Africa. The empirical evidence is based on the generalised method of moments. To make this assessment, inequality dynamics (i.e. the Gini coefficient, the Atkinson index and Palma ratio) are interacted with tourism (tourism receipts and tourists' arrivals) to establish inequality levels that should not be exceeded in order for tourism to promote financial access in the sampled countries. From the findings, inequality levels that should not be exceeded for tourism to promote financial access are provided: (i) 0.666 of the Atkinson index and 5.000 of the Palma ratio for tourism receipts to promote financial access and (ii) for tourist arrivals to enhance financial access, 0.586, 0.721 and 6.597 respectively, of the Gini coefficient, the Atkinson index, and the Palma ratio. Policy implications are discussed.
Keywords: O10; O40; Z3; Z32; 330; Tourism; Management; Financial access; Inequality; Africa; SustainableDevelopment